Submicrometer aerosol particle distributions in the upper troposphere over the mid-latitude North Atlantic - results from the third route of 'CARIBIC' - Hermann, M.; Brenningmeijer, C.A.M.; Slemr, F.; Heintzenberg, J.; Martinsson, B.G.; Schlager, H.; Velthoven van, P.F.J.; Wiedensohler, A.; Zahn, A.; Ziereis, H. (Tellus B: Chemical and Physical Meteorology, 2008)
Particle number and mass concentrations of submicrometer aerosol particles were determined for the upper troposphere over the mid-latitude North Atlantic within the Civil Aircraft for Regular Investigation of the Atmosphere Based on an Instrument Container project (CARIBIC, http://www.caribic-atmospheric.com). Between May 2001 and April 2002, 22 flights from Germany to the Caribbean were conducted using an automated measurement container on a B767 passenger aircraft. Spatial and seasonal probability distributions for ultrafine and Aitken mode particles as well as mass concentrations of particulate sulphur in 8–12 km altitude are presented. High particle number concentrations (mostly 2500–15 000 particles cm -3 STP) are particularly found in summer over the western North Atlantic Ocean close to the North American continent. The distributions together with an analysis of particle source processes show that deep vertical transport is the dominant process leading to most of the events with high particle number concentrations (>8000 particles cm -3 STP) for ultrafine particles as well as for Aitken mode particles. This study emphasizes the importance of deep vertical transport and cloud processing for the concentration of aerosol particles in the upper troposphere.